2016
DOI: 10.1038/cdd.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Restraining FOXO3-dependent transcriptional BMF activation underpins tumour growth and metastasis of E-cadherin-negative breast cancer

Abstract: Loss of cellular adhesion leads to the progression of breast cancer through acquisition of anchorage independence, also known as resistance to anoikis. Although inactivation of E-cadherin is essential for acquisition of anoikis resistance, it has remained unclear how metastatic breast cancer cells counterbalance the induction of apoptosis without E-cadherin-dependent cellular adhesion. We report here that E-cadherin inactivation in breast cancer cells induces PI3K/AKT-dependent FOXO3 inhibition and identify FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…Moreover, in HDGC there is a correlation between increased EGFR activation and the presence of mutant Ecadherin (Bremm et al 2008). In line with these findings it was recently shown that E-cadherin mutant cells specifically fail to transcriptionally up-regulate BMF because of AKT-dependent repression of FOXO3 (Hornsveld et al 2016). Since extensive work by the Brugge laboratory has established that BIM may play similar roles in breast cancer through integrin and GFR signaling-dependent cues (Reginato et al 2003), it appears that aberrant control of the proapoptotic BH3-only proteins is a key distal event in E-cadherin mutant cancer.…”
Section: Cell -Cell Adhesion and Cancersupporting
confidence: 52%
“…Moreover, in HDGC there is a correlation between increased EGFR activation and the presence of mutant Ecadherin (Bremm et al 2008). In line with these findings it was recently shown that E-cadherin mutant cells specifically fail to transcriptionally up-regulate BMF because of AKT-dependent repression of FOXO3 (Hornsveld et al 2016). Since extensive work by the Brugge laboratory has established that BIM may play similar roles in breast cancer through integrin and GFR signaling-dependent cues (Reginato et al 2003), it appears that aberrant control of the proapoptotic BH3-only proteins is a key distal event in E-cadherin mutant cancer.…”
Section: Cell -Cell Adhesion and Cancersupporting
confidence: 52%
“…Expression of FOXO3 and FOXO3.A3 was subsequently induced by feeding mice doxycycline-containing chow either early in tumor growth (2 weeks after surgery) or at a later stage at which tumors reached a size of approximately 100 mm 3 (measured weekly). Doxycycline alone has been shown not to influence mILC1 tumor growth in this model (4).…”
Section: Foxo3 Activation Represses Tumor Growth and Metastasismentioning
confidence: 57%
“…FOXOs have been suggested to be involved in regulating cell motility and migration in breast and colon cancer cells (6,8). In contrast, others and we have previously shown that FOXO activation induces anoikis in cancer cells (4,25). We therefore determined whether the observed decrease in metastatic potential upon both loss and gain of FOXO activity correlates with changes in cell migration or prevention of anchorage-independent survival.…”
Section: Foxos Provide Tumor Cells With Motility Invasiveness and Amentioning
confidence: 88%
See 1 more Smart Citation
“…This increase in BMF expression is critical for MEK162/BYL719-stimulated apoptosis, because knockdown of BMF significantly rescues cell death. BMF has recently been identified as a direct transcriptional target of FOXO3a (35), indicating that dephosphorylation of FOXO3a upon MEK and PI3K inhibition might contribute to transcriptional upregulation of BMF. In addition, BMF has been reported to be upregulated via internal ribosome entry sites (IRES)-mediated translation upon inhibition of cap-dependent translation (36).…”
Section: Changes In Pro-and Antiapoptotic Bcl-2 Proteins and Suppressmentioning
confidence: 99%